Protocols for treating patients with end‐stage renal disease: a survey of nephrology fellowships. (13th December 2016) - Perry, Maureen Munnelly; Howell, Scott; Patel, Nipa
ABSTRACT: Rationale/background: Approximately 14% of Americans are living with chronic kidney disease (CKD). The prevalence of end‐stage renal disease (ESRD), the result of progressing CKD continues to rise by 21, 000 per year. Currently, the only antibiotic prophylaxis guidelines for patients with ESRD undergoing dental treatment were published by the AHA in 2003.9 Presented in three parts, the first and second parts of this study found no consistent protocols amongst U.S. dental schools and U.S. GPRs and AEGDs, respectively. The goal of the third part of the project was to determine the current protocol being used to treat ESRD patients at U.S. nephrology fellowship programs. Methods and materials: An 18 multiple‐choice question survey was e‐mailed to 130 directors of nephrology fellowships within the U.S. regarding renal treatment protocol details and antibiotic prophylaxis for patients with renal disease. Results: Note that, 34.6% of respondents reported having an established renal treatment protocol. For programs with a protocol, 69% of programs reported following AHA guidelines. Conclusion: There is a lack of consistent, established protocols amongst U.S. nephrology fellowships. It is suggested that updated and evidence based guidelines for the safe treatment of patients be developed.